2006
DOI: 10.1038/sj.onc.1210107
|View full text |Cite
|
Sign up to set email alerts
|

Frequent epigenetic inactivation of cystatin M in breast carcinoma

Abstract: Cystatin M is a potent endogenous inhibitor of lysosomal cysteine proteases. In breast carcinoma, cystatin M expression is frequently downregulated. It has been shown that cystatin M expression suppressed growth and migration of breast cancer cells. We examined the methylation status of the CpG island promoter of cystatin M in four breast cancer cell lines (MDAMB231, ZR75-1, MCF7 and T47D), in 40 primary breast carcinoma and in corresponding normal tissue probes by combined bisulphite restriction analysis. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 25 publications
6
26
0
1
Order By: Relevance
“…In a subsequent study, methylation analysis of CST6 in breast cancer cell lines revealed an inverse correlation between CpG island hypermethylation and CST6 gene expression, and the extent of regional methylation in the proximal promoter was strongly correlated with the lack of CST6 expression (Rivenbark et al, 2006a). Consistent with these findings, several other studies have shown that CST6 is epigenetically regulated by DNA methylation-dependent silencing in breast cancer cell lines and primary invasive ductal carcinomas (Ai et al, 2006;Schagdarsurengin et al, 2006).…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“…In a subsequent study, methylation analysis of CST6 in breast cancer cell lines revealed an inverse correlation between CpG island hypermethylation and CST6 gene expression, and the extent of regional methylation in the proximal promoter was strongly correlated with the lack of CST6 expression (Rivenbark et al, 2006a). Consistent with these findings, several other studies have shown that CST6 is epigenetically regulated by DNA methylation-dependent silencing in breast cancer cell lines and primary invasive ductal carcinomas (Ai et al, 2006;Schagdarsurengin et al, 2006).…”
Section: Introductionsupporting
confidence: 55%
“…Ai et al showed that 12/20 (60%) primary breast tumors exhibit CST6 promoter hypermethylation, and microdissection of individual cells from select tumors revealed that methylation occurs in both DCIS and IDC cells (Ai et al, 2006). In a similar study, Schagdarsurengin et al showed that 24/40 (60%) breast carcinomas exhibited CST6 promoter hypermethylation, and that estrogen-receptor positive tumors were more frequently methylated than estrogen-receptor negative tumors (Schagdarsurengin et al, 2006). While CST6 is suggested to be epigenetically regulated through DNA methylation-dependent mechanisms in breast cancer cell lines and primary breast tumors that lack cystatin M protein expression, tumor metastases have not been examined for cystatin M expression or methylation status.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The availability of numerous breast carcinoma cell lines, with varying phenotypes (Soule et al, 1973;Cailleau et al, 1974;Thompson et al, 1992), has allowed for the identification of genes involved in the progression of breast cancer (Nagaraja and Kandpal, 2004;Nagaraja et al, 2006;Kagara et al, 2007;Schagdarsurengin et al, 2007). We have previously identified EphB6 as a molecule of interest in breast cancer by using representational difference analysis of MCF-7 and MDA-MB-231 cDNAs (Nagaraja et al, 2006) and semiquantitative RT-PCR (Fox and Kandpal, 2004).…”
Section: Introductionmentioning
confidence: 99%